MCM-41-supported platinum carbonyl cluster-derived asymmetric hydrogenation catalyst - Basu, Susmit; Paul, Himadri; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2005)
Anionic platinum carbonyl cluster has been ion paired with cinchonidium groups that are chemically bound to the surface of MCM-41 and fumed silica. In the hydrogenation of methyl pyruvate or acetophenone the fumed silica-based catalyst gives zero enantioselectivity, but under optimum conditions enantiomeric excesses of >90 and similar to40%, respectively, are obtained with the MCM-41-based catalyst. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: asymmetric catalysis; functionalized inorganic oxides; hydrogenation catalysts; platinum carbonyl cluster

MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster